OUTBOUND GAME MODEL TO DEVELOP INTERPERSONAL COMPETENCE OF PRIMARY SCHOOL STUDENTS - Nurhayati, Niken Fatimah; Sugiharto, Sugiharto (The Journal of Educational Development, 2016)
Playing is a useful learning experience for the physical, intellectual, social, moral and emotional development of children. The goal of this research is to produce a product of outbound game model that can be used to develop interpersonal competencies of students in elementary school. This research uses research and development approach. The data source is a qualitative and quantitative data obtained from the test results of small-scale, large-scale testing and evaluating the effectiveness of the product. The validity of the data is tested by validation experts and practitioners. Data analysis is carried out by  a qualitative descriptive approach with different percentages and t-test. The results of this study are: (1) there have been ten outbound game models which are effective to develop aspects of the initiative, assertiveness, openness, emotional support, and aspects of conflict management of students in elementary school, (2) it has been produced ten models games outbound effective to develop interpersonal competence of students in primary schools. The conclusions of this study are: there are problems of students in establishing effective communication with peers, so the model is a game designed to develop interpersonal competence and already meets the eligibility test. Suggestions of this research are: (1) the sport education teachers can try out the models of outbound games in exercise learning process, and (2) the teachers can use outbound game models to develop interpersonal competence on the lower and upper-grade students of elementary school.